Effects of lovastatin on biliary lipid secretion and bile acid metabolism in humans. - JC Mitchell; GM Logan; BG Stone; WC Duane (Journal of Lipid Research, 1991)
Lovastatin, an inhibitor of HMG-CoA reductase, lowers cholesterol saturation of bile. To determine the mechanism of this effect and further define the role of cholesterol synthesis in regulation of biliary lipid metabolism, we studied ten human volunteers in a control period and again after 5-6 weeks on lovastatin, 40 mg b.i.d. Mean sterol production from acetate in mononuclear leukocytes fell from 1.18 to 0.84 pmol/min per 10(6) cells on lovastatin (P less than 0.02). Concomitantly there was reduction in mean biliary secretion of cholesterol from 143 to 96 mumol/h (P less than 0.02). On lovastatin, mean pool size of bile acids by the Lindstedt method fell from 3193 to 2917 mumol (one-sided P = 0.05) and mean pool size by the one-sample method fell from 5158 to 4091 mumol (P less than 0.002). Lovastatin had no effect on mean fractional turnover rate of either cholic acid (0.77 vs. 0.74 day-1) or chenodeoxycholic acid (0.51 vs. 0.54 day-1). Mean total bile acid synthesis was lower on lovastatin (1443 vs. 1240 mumol/day), but the difference did not quite achieve statistical significance. In humans, inhibition of cholesterol synthesis by lovastatin lowers biliary cholesterol saturation by reducing cholesterol secretion into bile. Bile acid pool size, and perhaps bile acid synthesis, are also reduced by this inhibition.